Carpenter bees and the orchid of a princess: Natural pollination of Sirindhornia monophylla in Thailand - Kanok Orn Srimuang (2018)
Research on the pollination of Sirindhornia monophylla (Collett & Hemsl.) H. A. Pedersen & Suksathan was carried out in W Thailand, 2010-2012. The orchid is a nectariferous, non-autogamous and self-compatible terrestrial. During 120 man-hours of flower watching, three species of Ceratina were found to be the main pollinators, viz. C. (Ceratinidia) lieftincki van der Vecht, C. (C.) collusor Cockerell, C. (Pithitis) smaragdula (Fabricius), males and/or females. Braunsapis hewitti (Cameron) was a minor pollinator. Ceratina acquired pollinia on their forehead and in some cases they subsequently deposited massulae on the stigma of other S. monophylla flowers. Three further species, viz. Ceratina (Ceratinidia) accusator Cockerell, C. (C.) chiangmaiensis W., M. & L. and C. (C.) bryanti Cockerell, did not acquire pollinia; but in these cases all pollen in the visited flowers had already been removed by previous pollinators. Ceratina belongs to family Apidae, subfamily Xylocopinae, tribe Ceratinini, whereas Braunsapis belongs to tribe Allodapini. Fruit set was nearly 50%. This is the first detailed account on the pollination of a Sirindhornia species, a recently described genus with three species, all included in the Thai redlist.